2016
DOI: 10.1177/1087054716652478
|View full text |Cite
|
Sign up to set email alerts
|

Functioning of Young Adults With ADHD in the Military

Abstract: These results support a negative effect of ADHD on the functioning of young adults in a military setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 20 publications
2
5
1
Order By: Relevance
“…Another Israeli study found no difference in military service completion rates for individuals with ADHD as compared with previously established general completion rates, but the population size in this comparison was small, n=70 [14]. Two studies have investigated substance use in ADHD conscripts, but cigarette and alcohol dependence or other forms of substance abuse have not been reported to be increased among young adults with ADHD during military service [13,15].…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…Another Israeli study found no difference in military service completion rates for individuals with ADHD as compared with previously established general completion rates, but the population size in this comparison was small, n=70 [14]. Two studies have investigated substance use in ADHD conscripts, but cigarette and alcohol dependence or other forms of substance abuse have not been reported to be increased among young adults with ADHD during military service [13,15].…”
Section: Introductionmentioning
confidence: 82%
“…To our knowledge no such investigations have been carried out in the Nordic countries. One Israeli study of military conscripts with ADHD performed to assess military performance and general fitness by comparison with controls (ADHD cases n=14,655, controls n=29,310) found that the subjects with ADHD were more likely to be exempted from service, were less suitable for combat and required more sick leave [13]. Another Israeli study found no difference in military service completion rates for individuals with ADHD as compared with previously established general completion rates, but the population size in this comparison was small, n=70 [14].…”
Section: Introductionmentioning
confidence: 99%
“…Military service is yet another index for social function as it is highly demanding and in the Republic of Korea, mandatory for men 19 years of age or older. Although ADHD diagnosis does not automatically exempt an individual from military service, young men with ADHD are medically unsuitable for military service in general and show lower functioning (availing more sick days and seeking more health care) [114]. They are not only more likely to have comorbid personality and minor mood disorders but are significantly more at risk of developing post-traumatic stress disorder [114,115].…”
Section: Clinical Presentation Of Adult Adhdmentioning
confidence: 99%
“…Although ADHD diagnosis does not automatically exempt an individual from military service, young men with ADHD are medically unsuitable for military service in general and show lower functioning (availing more sick days and seeking more health care) [114]. They are not only more likely to have comorbid personality and minor mood disorders but are significantly more at risk of developing post-traumatic stress disorder [114,115]. A combination of lower intellectual capabilities and more psychiatric comorbidities may be predictive of poor adjustment outcomes in young adults with ADHD [68].…”
Section: Clinical Presentation Of Adult Adhdmentioning
confidence: 99%
“…The military is a highly demanding environment among various forms of social organization 12. Several studies have reported negative perceptions of individuals with ADHD in the military, lower functional level;12 higher indices of depression, anxiety, and substance abuse;13 shorter relationship spans;13 increased vulnerability to posttraumatic stress disorder;14 and lower quality of life 15. In Singapore, all male citizens who have reached the age of 18 years are legally mandated to enlist in the military, and those diagnosed with ADHD are assigned to administrative duties that do not provide easy accessibility to firearms, explosives, and ammunition 13…”
Section: Introductionmentioning
confidence: 99%